Current options and perspectives for the topical treatment of atopic dermatitis - Nowicki, Roman; Grubska-Suchanek, Elżbieta; Trzeciak, Magdalena; Wilkowska, Aleksandra (Dermatology Review/Przegląd Dermatologiczny, 2021)
Atopic dermatitis is one of the most common chronic and recurrent skin conditions, characterized by a complex genetic background, most commonly occurring in children. Its prevalence is still increasing. Despite existing methods of therapy (emollients, wet-wrap treatment, topical glucocorticoids, topical calcineurin inhibitors, antiseptics, antibiotics, phototherapy, elimination of irritants, patient education), the number of available topical preparations for the treatment of this chronic disease is limited. Topical glucocorticoids are the mainstay of the treatment of inflammatory changes. Calcineurin inhibitors should not be used under the age of two, and in the remaining patients, topical calcineurin inhibitors constitute the second-line therapy. Glucocorticoids can only be used for a strictly defined period of time and become gradually less effective during a long-term treatment (tachyphylaxis). Introduction of new, safe, topical preparations for the treatment of this chronic disease is imperative.